Resolusi Konflik Pendirian Rumah Ibadah (Studi Kasus Pendirian Masjid At-Tabayuuin Perumah Taman Villa Meruya Selatan, Kecamatan Kembangan, Kota Jakarta Barat - Muhammad Daffa Ramadhan; M. Ridwan Lubis (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research analyzes the conflict surrounding the establishment of Masjid At-Tabayyun in West Jakarta, highlighting the underlying causes, the steps taken by the Governor of DKI Jakarta in resolving it, and the implications of the conflict resolution. Utilizing a qualitative approach, the study employs observation, interviews, documentation, and relevant literature. Findings reveal that Masjid At-Tabayyun plays a significant role in fostering religious harmony, yet conflicts arise regarding its location. The Governor relocated the site and added functional aspects to make the mosque inclusive. This research has the potential to enhance interfaith harmony and serve as an example of conflict resolution for governmental bodies.